"We know this will be hard at the beginning, but better in the long term": understanding PrEP uptake in the general population in Eswatini. Issue 2 (1st February 2020) - Bärnighausen, Kate; Matse, Sindy; Hughey, Allison B.; Hettema, Anita; Bärnighausen, Till W.; McMahon, Shannon A.
ABSTRACT: Information regarding HIV pre-exposure prophylaxis (PrEP) for the general population is largely lacking, because the majority of PrEP demonstration projects have focused on key populations. This qualitative study examines barriers and facilitators to PrEP uptake and adherence among the general population in Eswatini, where PrEP is offered through public-sector primary-care clinics. We analysed 106 semi-structured in-depth interviews with healthcare workers ( n = 26), stakeholders ( n = 30), and clients who initiated, continued, declined or discontinued PrEP ( n = 50). Some healthcare workers and stakeholders feared that PrEP would reduce condom use and cause drug resistance, while some clients feared possible side effects and the reaction of family members when learning of PrEP use. At the same time, respondents across all groups valued that PrEP could be taken without partner knowledge or consent, and that PrEP was available via public sector clinics. Clients felt that PrEP relieved the fear of HIV infection and thus bolstered enjoyment during sex. Overall, respondents described the general population approach to PrEP delivery as enabling and life-improving, despite the above concerns. Respondents recommended to create community PrEP promotion and delivery, gain community leaders' approval and understanding of PrEP, shorten the PrEP initiation process, and target men and adolescent girls.